A coherent approach for analysis of the Illumina HumanMethylation450 BeadChip improves data quality and performance in epigenome-wide association studies. Issue 1 (December 2015) - Lehne, Benjamin; Drong, Alexander; Loh, Marie; Zhang, Weihua; Scott, William; Tan, Sian-Tsung; Afzal, Uzma; Scott, James; Jarvelin, Marjo-Riitta; Elliott, Paul; McCarthy, Mark; Kooner, Jaspal; et al.
Abstract DNA methylation plays a fundamental role in the regulation of the genome, but the optimal strategy for analysis of genome-wide DNA methylation data remains to be determined. We developed a comprehensive analysis pipeline for epigenome-wide association studies (EWAS) using the Illumina Infinium HumanMethylation450 BeadChip, based on 2, 687 individuals, with 36 samples measured in duplicate. We propose new approaches to quality control, data normalisation and batch correction through control-probe adjustment and establish a null hypothesis for EWAS using permutation testing. Our analysis pipeline outperforms existing approaches, enabling accurate identification of methylation quantitative trait loci for hypothesis driven follow-up experiments.